Skin manifestations corroborated by SARS-Cov-2 infection: an integrative literature review (Research, Society and Development, 2021)
Introduction: A growing body of literature on the cutaneous manifestations of patients with Covid-19 has been reported recently, suggesting that cutaneous lesions could be potential clinical features of the disease, particularly red spots on the hands, blisters on the trunk, and itchy urticaria. In some patients affected by the disease, red itchy patches of skin associated with skin inflammation were also observed. Objective: to investigate the most prevalent distribution, types and skin manifestations among patients with Covid-19 based on case reports, case series and prevalence studies worldwide. Methodology: This is a descriptive research of the integrative literature review type. The search was carried out through online access in the National Library of Medicine (PubMed MEDLINE), Scientific Electronic Library Online (Scielo), Cochrane Database of Systematic Reviews (CDSR), Google Scholar, Virtual Health Library (BVS) and EBSCO databases Information Services, September 2021. Results and Discussion: As rare as they may be, skin lesions are noticed a few days before major symptoms such as cough, fever, and shortness of breath. Generally, the lesions resemble other skin diseases. Redness, intense itching, blisters, welts, lumps and spots can reach different parts of the body such as the skin, nails and even mucous membranes. Conclusion: Despite the observation of cutaneous manifestations in patients with Covid-19, researchers are still seeking answers to the question of whether these cutaneous presentations are directly related to the virus itself or are complications of the infection.